Exploiting scavenger receptors in cancer immunotherapy: Lessons from CD5 and SR‐B1. Issue 7 (12th June 2017) - Vasquez, Marcos; Simões, Inês; Consuegra‐Fernández, Marta; Aranda, Fernando; Lozano, Francisco; Berraondo, Pedro
Abstract : Scavenger receptors (SRs) such as CD5 and SR‐B1 constitute macromolecular recognition and signaling platforms that can mediate both anti‐inflammatory and pro‐inflammatory responses. These activities can be exploited in cancer immunotherapy by modulating their pro/anti‐inflammatory activities. Abstract : Scavenger receptors (SRs) are structurally heterogeneous cell surface receptors characterized by their capacity to remove extraneous or modified self‐macromolecules from circulation, thus avoiding the accumulation of noxious agents in the extracellular space. This scavenging activity makes SRs important molecules for host defense and homeostasis. In turn, SRs keep the activation of the steady‐state immune response in check, and participate as co‐receptors in the priming of the effector immune responses when the macromolecules are associated with a threat that might compromise host homeostasis. Therefore, SRs built up sophisticated sensor mechanisms controlling the immune system, which may be exploited to develop novel drugs for cancer immunotherapy. In this review, we focus on the regulation of the anti‐tumor immune response by two paradigmatic SRs: the lymphocyte receptor CD5 and the more broadly distributed scavenger receptor class B type 1 (SR‐B1). Cancer immunity can be boosted by blockade of SRs working as immune checkpoint inhibitors (CD5) and/or by proper engagement of SRs working as innate danger receptor (SR‐B1). Thus, these receptors illustrate both the complexity of targeting SRs in cancer immunotherapy and also the opportunities offered by such an approach.